Residual effect of BNI by Brachiaria humidicola pasture on nitrogen recovery and grain yield of subsequent maize - Karwat, Hannes; Moreta, Danilo; Arango, Jacobo; Núñez, Jonathan; Rao, Idupulapati M.; Rincón, Álvaro; Rasche, Frank; Cadisch, Georg (Springer, 2017)
Background and Aims: The forage grass Brachiaria humidicola (Bh) has been shown to reduce soil microbial nitrification. However, it is not known if biological nitrification inhibition (BNI) also has an effect on nitrogen (N) cycling during cultivation of subsequent crops. Therefore, the objective of this study was to investigate the residual BNI effect of a converted long-term Bh pasture on subsequent maize (Zea mays L.) cropping, where a long-term maize monocrop field (M) served as control.